Validity and feasibility of remote measurement systems for functional movement and posture assessments in people with axial spondylarthritis - Erin Hannink; Maedeh Mansoubi; Neil Cronin; Benjamin Wilkins; Ali A. Najafi; Benjamin Waller; Helen Dawes (Healthcare Technology Letters, 2022)
Abstract Introduction: This study aimed to estimate the criterion validity of functional movement and posture measurement using remote technology systems in people with and without Axial spondylarthritis (axSpA). Methods: Validity and agreement of the remote‐technology measurement of functional movement and posture were tested cross‐sectionally and compared to a standard clinical measurement by a physiotherapist. The feasibility of remote implementation was tested in a home environment. There were two cohorts of participants: people with axSpA and people without longstanding back pain. In addition, a cost‐consequence analysis was performed. Results: Sixty‐two participants (31 with axSPA, 53% female, age = 45(SD14), BMI = 26.6(SD4.6) completed the study. In the axSpA group, cervical rotation, lumbar flexion, lumbar side flexion, shoulder flexion, hip abduction, tragus‐to‐wall and thoracic kyphosis showed a significant moderate to strong correlation; in the non‐back pain group, the same measures showed significant correlation ranging from weak to strong. Conclusions: Although not valid for clinical use in its current form, the remote technologies demonstrated moderate to strong correlation and agreement in most functional and postural tests measured in people with AxSA. Testing the CV‐aided system in a home environment suggests it is a safe and feasible method. Yet, validity testing in this environment still needs to be performed.